(untitled) (International Conference on Computers in Education, 2020)
Studies have shown that transactional distance negatively impacts student learning. In the context of learning, distance pertains to the geographic, pedagogical, and psychological gap between instructors and students. This perception of distance is magnified in online learning because instructors and students do not meet face to face. The gaps involve not only the geographic aspect. Another gap is pedagogical, which depends on the online course’s design and structure flexibility and how these align with the students’ level of autonomy. Still, another gap is psychological, which relates to how students perceive how much the teacher is accessible or disengaged (level of dialogue) and with students’ academic self-efficacy assessments. This paper describes how we could reduce the transactional distance between instructor and students by deliberately designing and conducting mostly asynchronous classes on programming for business students but with the right blend of non-lecture synchronous activities during tight lockdown due to COVID-19. We explain what used to work well before the pandemic where classes were onsite and face-to-face and what mechanisms we used to overcome the lockdownrelated gaps. The course was held during Intersession and only had less than six weeks. Based on students’ grades and general sentiments, the results were in line with expected learning outcomes, and miscellaneous feedback and comments from students were positive.